Deradicalization Through Multicultural and Local Wisdom Literacies Based Teaching Model at Salaf and Kholaf Pesantren in West Java - Tedi Rohadi (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2017)
Indonesia has been a country with multi-ethnics, cultures, and religions. These diversities become its own wealth and treasures as well as dangers. The differences will create dynamic and meaningful human lives. On the other hand, they posit potential radicalization and conflicts that will explode anytime due to their differing meaning and perception. Education is a solution since it plays a role of social reconstruction. It can not only maintain ethnic, linguistic and cultural diversity but also achieve social inclusion, equity and intercultural understanding. The paper aims to report the result of the first stage of research and development study in developing instructional model based on multicultural, local wisdom, and literacy perspectives at Salaf and Kholaf Pesantren in West Java. The model consists of three variables which are variable of context, process, and product. The expected product is the students’ competencies and awareness of how to cater differences in order to have moderate perspective.